Pixellated Perovskite Photodiode on IGZO Thin Film Transistor Backplane for Low Dose Indirect X-Ray Detection - Taoyu Zou (IEEE, 2021)
The integration of perovskite photodetectors with thin-film transistor (TFT) backplane or complementary metal-oxide-semiconductor CMOS circuit is a key step towards prototyping perovskite-based image sensors. Here, we demonstrate a pixel configuration for indirect X-ray detection comprising of IGZO TFTs and perovskite photodiodes (PDs). The perovskite photodiode is patterned by a two-step deposition method. Our integrated TFT/PD pixel shows a weak light detection capability down to 4 nW cm−2 and a fast-transient response to the pulse light and gate switching. Combining with a CsI scintillator, the integrated pixel achieves a specific X-ray sensitivity of 8.2 $8.2 × 10^{2} μ C mGy_{\text {air }}^{-1} ~cm^{-3}$ . Theoretically, with a state-of-the-art scintillator, the new pixel can provide a detectable signal for X-ray imaging at a dose rate as low as $10 μ Gy_{\text {air }} s^{-1}$ . This work provides an advanced pixel design for high resolution, high sensitivity, and high frame-rate flat-panel imager.